Faster the better: a reliable technique to sample anopluran lice from large hosts - Leonardi, María Soledad (2014)
Among Anoplura,the family Echinophthiriidae includes those species that infest mainly the pinnipeds. Working with large hosts implies methodological considerations as the time spent in the sampling, and the way in that the animal is restrained. Previous works on echinophthiriids combined a diverse array of analyses including field counts of lice and in vitro observations. To collect lice, the authors used forceps,and each louse was collected individually. This implied a long manipulation time, i.e., ≈60 min and the need to physically and/or chemically immobilize the animal. The present work described and discussed for the first a sample technique that minimized the manipulation time and also avoiding the use of anesthesia. This methodology implied combing the host?s pelage with a fine-tooth plastic comb, as used in the treatment of human pediculosis, and keeping the comb with the lice retained in a Ziploc® bag with ethanol. This technique was used successfully in studies of population dynamic, habitat selection, and transmission pattern, being a reliable methodology. Lice are collected entirely and are in a good condition to prepare them for mounting for studying under light or scanning electron microscopy. Moreover, the use of the plastic comb protects from damaging taxonomically important structures as spines being also recommended to reach taxonomic or morphological goals.